An upstream transcription factor, USF (MLTF), facilitates the formation of preinitiation complexes during in vitro chromatin assembly. - Workman, J L (1990)
During in vitro chromatin assembly the formation of transcription complexes is in direct competition with the assembly of promoter sequences into nucleosomes. Under these conditions the fold stimulation of transcription by an upstream transcription factor (USF) was greater than that observed in the absence of nucleosome assembly. Function of USF during nucleosome assembly required the simultaneous presence of the TATA box binding protein TFIID. Unlike TFIID, USF alone was unable to prevent repression of the promoter during nucleosome assembly. Furthermore, USF displayed reduced or no transcriptional stimulatory activity when added to previously assembled minichromosomes. Under conditions of nucleosome assembly, USF increased the number of assembled minichromosomes which contained stable preinitiation complexes. Subsequent to assembly, the rate at which preformed complexes initiated transcription appeared to be independent of the presence of USF. Thus USF potentiated the subsequent transcriptional activity of the promoter indirectly, apparently by increasing the rate or stability of TFIID binding. This activity resulted in the promoter becoming resistant to nucleosome mediated repression. These observations suggest that some ubiquitous upstream factors, e.g. USF, may play an important role in establishing the transcriptional potential of cellular genes during chromatin assembly.